Information-Processing Demands as a Determinant of Ceo Compensation - Henderson, Andrew D.; Fredrickson, James W. (Academy of Management Journal, 1996)
Early research found little relationship between CEO pay and firm performance. Therefore, recent work on CEOs' compensation has focused less on the substantive nature of the job performed by such executives and more on the social and political context in which their pay is set. This study returns attention to the substantive nature of CEOs' jobs. Specifically, we argue that CEOs are paid for the level of information processing that their jobs require. Results from four industries support this view: chief executive compensation was higher in firms whose diversification strategy, approach to technology, and top management team structure placed particularly high information-processing demands on their CEOs.